1992
DOI: 10.1073/pnas.89.9.3741
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin-mediated inhibition of bovine calcineurin by cyclophilins A and B.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 44 publications
7
98
1
1
Order By: Relevance
“…A long-standing paradox concerning the regulation of CN is that the CN phosphatase activity towards pRII substrate was strongly inhibited by both CyPA-CsA and FKBP12-FK506, while the activity of CN towards pNPP was stimulated by approximately 4-fold in the presence of the drug complexes [28,29]. We confirmed these results for WT CN β.…”
Section: Further Evidence For the Multi-level Activation Of Cnsupporting
confidence: 79%
“…A long-standing paradox concerning the regulation of CN is that the CN phosphatase activity towards pRII substrate was strongly inhibited by both CyPA-CsA and FKBP12-FK506, while the activity of CN towards pNPP was stimulated by approximately 4-fold in the presence of the drug complexes [28,29]. We confirmed these results for WT CN β.…”
Section: Further Evidence For the Multi-level Activation Of Cnsupporting
confidence: 79%
“…A Ca 2+ -dependent, CsA-inhibitory protein phosphatase activity was also detected Figure 4, pCyP B-CsA inhibited calcineurin activity with Ki of 4 9 0 nM. This value is comparable to the potency of the complexes formed by CsA and mammalian CyPs (Swanson et al, 1992;Bram et al, 1993). Neither CsA nor pCyP B alone inhibited calcineurin activity (data not shown).…”
Section: Complex Of Pcyp B-csa Inhibits Calcineurin Activitysupporting
confidence: 49%
“…Several cyclophilin-CsA complexes have been shown to inhibit the Ca 2+ calmodulin-dependent protein phosphatase calcineurin and to block T cell activation (Swanson et al, 1992;Bram et al, 1993). In an earlier article (Luan et al, 1993), we reported that CsA blocks a Ca 2+ -dependent signal transduction pathway in guard cells of fava bean.…”
Section: Complex Of Pcyp B-csa Inhibits Calcineurin Activitymentioning
confidence: 99%
“…Ratiometric determinations were also made in cells treated with the Ca 2ϩ chelators BAPTA (Molecular Probes) and EDTA. Calcineurin Substrate Preparation-R II peptide was prepared and radiolabeled with [␥-32 P]ATP by cAMP-dependent protein kinase as described (25,26). Briefly, R II peptide (0.15 mM) was phosphorylated in 1 ml of phosphorylation reaction buffer (50 mM MOPS, pH 7.0, 2 mM MgSO 4 , 0.3 mM ATP, 2500 units of the catalytic subunit of cAMP-dependent protein kinase and 833 Ci/mmol of [␥-32 P]ATP) for 3 h at 30°C.…”
Section: ϩmentioning
confidence: 99%